Refining GAL4-driven transgene expression in Drosophila with a GAL80 enhancer-trap. - Suster, M.L.; Seugnet, L.; Bate, M.; Sokolowski, M.B. (genesis, 2004)
We constructed an enhancer-trap element, P[GAL80], that encodes the yeast GAL80 repressor to refine expression of transgenes driven by the binary GAL4/UAS system. GAL80 blocks GAL4 activity by binding to its transcriptional activation domain. We screened GAL80 enhancer-traps for repression of GAL4-induced green fluorescent protein (GFP) in the intact larval nervous system. We selected one line that repressed GFP in a large set of cholinergic neurons. This line was used to refine GFP expression from a set of over 200 neurons to a subset of 20 neurons in a preselected GAL4 line. Expression of tetanus neurotoxin, a potent blocker of neurotransmitter release, in these 20 neurons reproduced an aberrant larval turning behavior previously assigned to the parental set of 200 neurons. Our results suggest that targeted GAL80 expression could become a useful means of spatially refining transgene expression in Drosophila.